2019
DOI: 10.1016/j.ydbio.2018.01.014
|View full text |Cite
|
Sign up to set email alerts
|

A speculative outlook on embryonic aneuploidy: Can molecular pathways be involved?

Abstract: The journey of embryonic development starts at oocyte fertilization, which triggers a complex cascade of events and cellular pathways that guide early embryogenesis. Recent technological advances have greatly expanded our knowledge of cleavage-stage embryo development, which is characterized by an increased rate of whole-chromosome losses and gains, mixoploidy, and atypical cleavage morphokinetics. Embryonic aneuploidy significantly contributes to implantation failure, spontaneous miscarriage, stillbirth or co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 167 publications
(172 reference statements)
1
30
0
Order By: Relevance
“…Given that inappropriate expression of maternally-inherited signaling factors has been suggested to regulate early mitotic chromosome segregation in mammalian preimplantation embryos (Mantikou et al, 2012; Taylor et al, 2014; Tsuiko et al, 2019), we next determined whether BUB1B deficiency impacted the expression of other key genes ( Fig. 1A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that inappropriate expression of maternally-inherited signaling factors has been suggested to regulate early mitotic chromosome segregation in mammalian preimplantation embryos (Mantikou et al, 2012; Taylor et al, 2014; Tsuiko et al, 2019), we next determined whether BUB1B deficiency impacted the expression of other key genes ( Fig. 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…This is in spite of findings that mitotic errors are equally or more prevalent than meiotic errors and arise independently of maternal age or fertility status (Chavez et al, 2012; Chow et al, 2014; McCoy, Demko, Ryan, Banjevic, Hill, Sigurjonsson, Rabinowitz, Fraser, et al, 2015; McCoy, Demko, Ryan, Banjevic, Hill, Sigurjonsson, Rabinowitz, & Petrov, 2015; Vanneste et al, 2009). Since the first three mitotic divisions are the most error-prone and activation of the embryonic genome does not occur until the 4- to 8-cell stage in the majority of mammals (Braude, Bolton, & Moore, 1988; Dobson et al, 2004; Plante, Plante, Shepherd, & King, 1994), it was suggested that maternally-inherited signaling factors regulating early mitotic chromosome segregation may be lacking or compromised in mammalian preimplantation embryos (Mantikou, Wong, Repping, & Mastenbroek, 2012; Taylor et al, 2014; Tsuiko et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, mammalian species such as human [ 11,76,77 ] non‐human primates [ 78,79 ] , farm animals [ 80–84 ] and murine [ 74 ] have been reported to have chromosomal mosaicism in pre‐implantation embryos. [ 85 ] Their reproductive strategy involves longer gestation times with fewer progeny. So why not have an efficient mechanism in place guarding chromosomal behavior in order to increase the chances of viable offspring?…”
Section: Different Life Strategies Are Associated With Different Evolmentioning
confidence: 99%
“…Proper segregation of both maternal and paternal haploid chromosome sets into each blastomere is required at the first division of the zygote to form a developmentally competent 2-cell embryo. Otherwise, developmental defects arise in embryos due to aneuploidy or polyploidy [19]. Polyploidy describes genomes with more than two complete sets of chromosomes, and is observed in several species including plants and yeasts [20].…”
Section: Introductionmentioning
confidence: 99%